First record of Coronida glasselli (Stomatopoda: Coronididae) for Costa Rica (Isla del Coco National Park, Eastern Tropical Pacific) - Salas-Moya, Carolina (2016)
Stomatopods are a small group of marine and estuarine crustaceans that inhabit several marine ecosystems including deep, shallow waters, and intertidal zones. Six species from five families have been reported from the Park. We add Coronida glasselli Manning, 1976 from rocky reef environments at Isla del Coco. In the Eastern Tropical Pacific the species was reported only from Isla Gorgona, Colombia. There are species from Isla Uva, Panamá in the National Museum of Natural History, Washington DC.